2007
DOI: 10.1086/511190
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Radio Transient at High Galactic Latitude

Abstract: Radio transient surveys at high Galactic latitudes have not been conducted until now, as they require long periods of observation. We have constructed a full-time survey facility, the eight-element Nasu Spherical Dish Array, for radio transients and pulsars. The observing frequency is 1.4 GHz, and the bandwidth is 20 MHz. We started the radio transient survey project in 2004 and have detected some radio transients. In this paper, we report the first radio transient detected in this project. During 11 days of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Separately, Kuniyoshi et al (2006aKuniyoshi et al ( , 2006bKuniyoshi et al ( , 2007, Niinuma et al (2007Niinuma et al ( , 2009, Kida et al (2008), and Matsumura et al (2009) reported on a search for radio transients using an 518 OFEK ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Separately, Kuniyoshi et al (2006aKuniyoshi et al ( , 2006bKuniyoshi et al ( , 2007, Niinuma et al (2007Niinuma et al ( , 2009, Kida et al (2008), and Matsumura et al (2009) reported on a search for radio transients using an 518 OFEK ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Nine bursts -named the WJN transients -in excess of 1 Jy have been discovered using drift scan observations with the Waseda Nasu Pulsar Observatory at 1.4 GHz (summarized in Matsumura et al 2009, but also see Kuniyoshi et al 2007;Niinuma et al 2007;Kida et al 2008;Niinuma et al 2009 for further details). These are some of the brightest transients reported in the literature and so far remain unexplained.…”
mentioning
confidence: 99%
“…One transient candidate was reported and a thorough discussion of the variable radio sources within the field was given. Matsumura et al (2009) summarise the detections of nine candidate transient sources from the Nasu 1.4-GHz widefield survey (see Kuniyoshi et al 2007;Matsumura et al 2007;Niinuma et al 2007Niinuma et al , 2009Kida et al 2008, for full details). The sources were detected in a drift scan mode and have flux densities greater than 1 Jy, with typical timescales of minutes to days.…”
Section: Gigahertz Surveysmentioning
confidence: 99%